Healthy Eating for Elders: Food Storage Guide - Jennifer Hillan (EDIS)
If you don’t shop for groceries often, you probably try to buy food that will last until your next trip to the store. To help you learn how much to buy, here are storage guidelines for some perishable foods. Tips: Store fruits and vegetables (except potatoes and tomatoes) in the crisper drawer of your refrigerator, and keep your refrigerator below 40EF. Store potatoes and tomatoes at room temperature. This is document FCS 8695-ENG, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: February 2005.